IMPORTED RAW MATERIAL INVENTORY CONTROL SYSTEM AS AN EFFORT TO MINIMIZE INVENTORY COST (A CASE STUDY IN PT APPAREL ONE INDONESIA) - Novelia Selvy Kurniasari; Yusmar Ardi Hidayat; Nur - Rini (Politeknik Negeri Semarang, 2016)
This study aims to forecast the polyesterusage for the upcoming 12 months and to findout the suitable method of imported rawmaterial inventory control in PT Apparel OneIndonesia by comparing and analyzing theimplementation of JIT concept and EOQmethod as well as to determine the safetystock and reorder point in inventoryprocurement of the company. The data usedin this study are secondary data of importedraw material procurement system, the costsassociated with raw materials inventory2015-2016 and other relevant data. Polyesteris observed since it is imported fabric rawmaterial which mostly used in the company.The polyester usage predicted by regressionis continuously increases per month. Theforecasting result can be accepted becausethe tracking signal value is not more than ± 4.Whereas, EOQ method is more suitable to beused by the company since the inventory costis lower than the cost applying JIT concept. Itis possible to save 13% or 9,512,693.3 IDR.Moreover, by applying EOQ method, it alsodetermines the reorder point (ROP) andsafety stock inventory to guarantee thesmoothness of production activities. Thecompany can purchase raw materials whenthe quantity of inventory is amounted to375.547 yards (ROP), while the safety stockof polyester fabric is 43,006 yards.